2017
DOI: 10.1371/journal.pone.0168325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Oral Doses of Sodium Chloride on the Basal Acid-Base and Mineral Status of Exercising Horses Fed Low Amounts of Hay

Abstract: The provision of NaCl, according to current recommendations, to horses in moderate work has been shown to induce immediate postprandial acidosis. The present study aimed to clarify whether this NaCl induced acidosis i) persists beyond the immediate postprandial period, and ii) is still present after a 2 week adaptation period. Six adult warmblood mares in moderate work received daily 1.00 kg hay per 100 kg body weight (bwt) only together with 0.64 kg unprocessed cereal grains/100 kg bwt.d as fed basis. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 31 publications
3
17
4
1
Order By: Relevance
“…Another study focused on effects of dosages of NaCl on mineral status of exercising horses observed serum concentrations of chlorides in horses subjected to similar load as in our experiment [ 15 ]. Their findings shown concentrations ranged from 101 to 105 mmol/l which is in agreement with our results that ranged between 101.7 to 102.9 mmol/l over the course of the experiment and the values were within reference range.…”
Section: Discussionmentioning
confidence: 99%
“…Another study focused on effects of dosages of NaCl on mineral status of exercising horses observed serum concentrations of chlorides in horses subjected to similar load as in our experiment [ 15 ]. Their findings shown concentrations ranged from 101 to 105 mmol/l which is in agreement with our results that ranged between 101.7 to 102.9 mmol/l over the course of the experiment and the values were within reference range.…”
Section: Discussionmentioning
confidence: 99%
“…Proline used at higher concentrations may prove to be lethal for the plant, causing ultra-structural damages leading to ROS generation [178]. The effective dose of proline varies with genotype and plant developmental stage [179][180][181][182]. Proline accumulation has been reported for drought sensitive and tolerant barley genotypes grown under saline conditions.…”
Section: Salinity and Prolinementioning
confidence: 99%
“…This is in agreement with the study of Schryver et al (1987), where a diet containing 5% NaCl exerted no adverse effect on mature gelding ponies. Similarly, warmblood horses in moderate work receiving up to 100‐g NaCl/day together with the concentrates remained healthy (Zeyner et al, 2017).…”
Section: Discussionmentioning
confidence: 99%